Analisis Faktor – Faktor yang Mempengaruhi Produksi Sulaman Tangan di Home Industry Elok Yun Desa Naras 1 Kota Pariaman - Atiqah Citra Insani; Amsah Hendri Doni (ARZUSIN, 2026)
Although the influence of labor and raw materials on production has been widely studied, research that specifically discusses home industry-based hand embroidery production remains limited. This study aims to analyze the influence of labor and raw materials on hand embroidery production at Elok Yun Home Industry, Naras 1 Village, Pariaman City. This study used a quantitative approach with a survey design, involving 30 respondents selected using saturated sampling. Data were collected through questionnaires, observation, and documentation, then analyzed using multiple linear regression. The results showed that labor had a positive and significant effect on hand embroidery production, whereas raw materials did not have a significant partial effect. However, simultaneously, labor and raw materials had a significant effect on production. The coefficient of determination showed that the two variables were able to explain most of the variation in production, while the remainder was influenced by other factors outside the research model. These findings contribute to the development of production theory studies, particularly in the context of labor-intensive industries based on traditional skills, and expand understanding of the dominant role of labor compared with raw materials in the production process. The conclusion of this study emphasizes the importance of improving labor quality and skills as a strategy to encourage the productivity of home industry-based hand embroidery industries.